PEMBERDAYAAN MASYARAKAT DESA SEPANYUL DALAMPROGRAMPENGEMBANGAN PENDIDIKAN RELIGIUS - Hayyin Iffatul Hana; Adeliya Siti Napi'ah; Dwi Setiyorini (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2022)
One of the problems that occur in society in general is the lack of a sense of being aware of the potential or abilities possessed by each individual around them that they might be able to use. With this potential, the community can better build and develop their learning system in their respective hamlets, so that their environmental conditions are more advanced and can help other communities who are less than optimal in education. The problem that will be raised in the community service program through this KKN (Real Work Class) activity is to increase various kinds of community activities in the field of religious and social education. This community service program was carried out in Sepanyul Village, Gudo District, Jombang Regency on April 22 – May 25, 2019 using the PAR method and a case study approach, namely by observing and describing the situation in Sepanyul Village more deeply. Data collection was carried out by several strategies, namely, discussions with Field Supervisors (DPL), in-depth interviews with the Village Head (Kades) of Sepanyul, the head of the hamlet (Kasun), community leaders and religious leaders in the village of Sepanyul which aimed to find information related to existing problems. in the village of Spain. Discussion of solutions to overcome problems in the village of Sepanyul. As well as the implementation of work programs as a form of implementing solutions to the problems encountered. The result of this community service program is the realization of a program to increase activities in the field of religious and social education, such as implementing the banjari prayer program, madin/TPQ assistance, Jam'iyah yasinan assistance, tutoring, and Clean Friday Activities.